Electrochemical characterisation of heat-treated metal and non-metal anodes using mud in microbial fuel cell - Raba'atun Adawiyah Shamsuddin,; Wan Ramli Wan Daud,; Kim, Byung Hong; Jamaliah Md. Jahim,; Mimi Hani Abu Bakar,; Wan Syaidatul Aqma Wan Mohd Noor,; Rozan Mohamad Yunus, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Microbial fuel cells (MFCs) have a high potential application for simultaneous wastewater treatment and electricity generation. However, the choice of the electrode material and its design is critical and directly affect their performance. As an electrode of MFCs, the anode material with surface modifications is an attractive strategy to improve the power output. In this study, stainless steel (SS) and carbon steel (CS) was chosen as a metal anode, while graphite felt (GF) was used as a common anode. Heat treatment was performed to convert SS, CS and GF into efficient anodes for MFCs. The maximum current density and power density of the MFC-SS were achieved up till 762.14 mA/m2 and 827.25 mW/m2, respectively, which were higher than MFC-CS (641.95 mA/m2 and 260.14 mW/m2) and MFC-GF (728.30 mA/m2 and 307.89 mW/m2). Electrochemical impedance spectroscopy of MFC-SS showed better catalytic activity compared to MFC-CS and MFC-GF anode, also supported by cyclic voltammetry test.